ANALISIS PENGOPTIMALAN FLYOVER TEUKU CIK DITIRO MELALUI PENGATURAN INTENSITAS BANGUNAN DI KOTA BANDAR LAMPUNG - Balqis Febriyantina Gunari; Zenia F Saraswati (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
The city of Bandar Lampung as the capital of Lampung Province causes a high number of movements so that traffic jams cannot be avoided on several roads in the City of Bandar Lampung. Responding to these problems, the city government of Bandar Lampung has carried out many flyovers as an effort to increase road capacity to meet high demand and is projected to continue to increase. The Teuku Cik Ditiro flyover which is included in the Kemiling District area is one of the three flyovers built in 2017-2018. This research was conducted to determine the impact caused by the construction of flyovers on traffic performance in both internal and external areas using a VCR projection on the affected roads. It will be known that the saturation time of the existing road and flyover is known with the method of sensitivity analysis through gradual loading. The results showed that the construction of the flyover caused the existing road conditions and the flyover side to become saturated in 2028-2038. So it is important for the Government of Bandar Lampung to anticipate this by setting the building intensity rules. The types of activities that exist in the internal region and the external region are dominated by trade and services. Setting the building intensity as a form of flyover optimization is important to pay attention to the direction of the spatial structure plan which also traffic loads affects on existing roads and flyovers.